2007
DOI: 10.33762/mjbu.2007.48140
|View full text |Cite
|
Sign up to set email alerts
|

The Total Antioxidant Status in Cigarette Smoking Individuals

Abstract: Active smokers are exposed to reactive free radicals that are present in cigarette smoke. Oxygen free radicals, including superoxide, hydroxyl radicals, peroxyl radical hydrogen peroxide and singlet oxygen, are highly reactive species that can cause a wide spectrum of cell damage including enzyme inactivation, lipid peroxidation, protein and lipoprotein oxidation, and DNA damage. Free radicals are believed to be involved in the pathogenesis of cardiovascular diseases and cancer. The purpose of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…One of the most important factors that make a contribution to oxidative stress is smoking. Cigarette smoke contains a great number of oxidants and this situation is held responsible for many negative effects caused by smoking . Similar to the literature knowledge, in our study, TAS value was statistically lower in smokers than in non‐smokers; TOS and OSI values were statistically higher in smokers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…One of the most important factors that make a contribution to oxidative stress is smoking. Cigarette smoke contains a great number of oxidants and this situation is held responsible for many negative effects caused by smoking . Similar to the literature knowledge, in our study, TAS value was statistically lower in smokers than in non‐smokers; TOS and OSI values were statistically higher in smokers.…”
Section: Discussionsupporting
confidence: 90%
“…Smokers have low antioxidant values than non‐smokers which may be because of the presence of high amounts of free radicals present in cigarette smoke that generate an oxidative stress in the smoker bodies, causing an exhaustion of the antioxidants of the body. In a study performed by Mahmood et al in Mosul on 20 active smokers and 20 non‐smokers, TAS average was found significantly and statistically lower in smokers than in non‐smokers. Similar to our study, in the study of Kose et al, TOS and OSI average was high in smokers and TAS average was significantly lower in smokers than in non‐smokers.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Hammo Mahmoud et al 2 measured plasma level of TAoC in smokers’ antecubital venous blood using a similar test to that of the present study and showed a significant reduction in total antioxidant status in smokers.…”
Section: Discussionsupporting
confidence: 66%